1998
DOI: 10.1007/bf02498153
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic reduction of acetylene and dinitrogen with the participation of the iron-molybdenum cofactor of nitrogenase and synthetic polynuclear molybdenum(iii) complexes

Abstract: Catalytic reduction of acetylene and dinitrogen was carried out by sodium, zinc, and europium amalgams in the presence of polymolybdenum clusters and the iron-molybdenum cot'actor of nitrogenase isolated from the enzyme. The activity of both catalysts toward acetylene changes in the sequence Zn(Hg) < Eu(Hg) < Na(Hg), increasing as the redox potential of the reducing agent is shifted to the negative region. The catalytic reduction of N;~ occurs only by the action of sodium and europium amalgams and only in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…So far no one has been able to do that, but a first step in this direction has been taken by Pickett et al 25 who have have reported that for large enough negative bias, H 2 can be produced, showing that the chemical potential of (H ϩ ϩe Ϫ ) in the active site of the enzyme can be raised electrochemically above that of hydrogen in H 2 . Shilov et al 40 have catalytically reduced acetylene by means of the FeMoco and various amalgams as reductants. In this connection it is also relevant to note that there has been several reports on the protolysis of N 2 containing transition metal complexes under strongly reducing conditions.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…So far no one has been able to do that, but a first step in this direction has been taken by Pickett et al 25 who have have reported that for large enough negative bias, H 2 can be produced, showing that the chemical potential of (H ϩ ϩe Ϫ ) in the active site of the enzyme can be raised electrochemically above that of hydrogen in H 2 . Shilov et al 40 have catalytically reduced acetylene by means of the FeMoco and various amalgams as reductants. In this connection it is also relevant to note that there has been several reports on the protolysis of N 2 containing transition metal complexes under strongly reducing conditions.…”
Section: Figmentioning
confidence: 99%
“…It cannot be excluded that the enzyme has a structure that facilitates the proton transfer particularly well, and that it is difficult to obtain equally good conditions at a metal surface. On the other hand, it is known that even the isolated cofactor can produce H 2 , 25 can protonate acetylene, 40 and binds CO in much the same way as in the enzyme. 26 Recently it has been reported that ammonia was produced electrochemically by a Pd catalyst on a proton conducting oxide.…”
Section: Gentle N 2 Hydrogenationmentioning
confidence: 99%
“…For example, the system with Mg-Mo clusters as catalysts and Na/Hg as electron donor reduces actively N 2 to N 2 H 4 and NH 3 , and even a weaker reducing agent (Eu/Hg) can be used for this reaction in the presence of a more acidic proton source (thiophenol). 25, 26 For this sys tem, in particular, it has been studied the dependence of the rate of catalytic С 2 Н 2 reduction on the specified po tential of the zinc amalgam cathode. The rate showed an exponential dependence plotted on the electrode poten tial.…”
Section: Resultsmentioning
confidence: 99%
“…The Mg-Mo complex, unlike FeMoco extracted from the protein, effi ciently catalyzes the reduction of N 2 to hydrazine and ammonia (see, for example, Ref. 13 and references cited therein). It was of interest to determine the characteristics of the dinitrogen complex formed at the first step of N 2 activation to compare them with the results obtained for the FeMoco catalyst.…”
Section: Methodsmentioning
confidence: 99%
“…12 The con centration of ammonia was determined by the indophenol method modified as described previously. 13 The gaseous reaction products, viz., ethylene, ethane, and methane, were analyzed by gas chromatography on a Biochrom chromatograph (column filled with activated alumina (0.25-0.5 mm), column temperature 90 °C, argon as the carrier gas, flame ionization detector).…”
Section: Momentioning
confidence: 99%